Analisis Keaktifan Belajar Siswa Sekolah Dasar menggunakan Aplikasi Wordwall - Nuning Hardi Yanti; Duwi Nuvitalia; Noor Miyono; Nur Rizkiyati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2023)
The activeness of student learning can be used as one of the keys to success in the learning process. To obtain an optimal learning process, learning media is needed to help students be active and easily understand the material. In this digital era, teachers must also be able to use technology-based learning media such as wordwall applications. The wordwall application is an application that contains a variety of educational games that can be applied as learning media. This study aims to analyze student learning activeness in using the wordwall application in class IVC SDN Karanganyar Gunung 02. This research includes research that uses descriptive qualitative methods. Data collection uses techniques in the form of observation, interviews, and document search. This study used instruments, namely observation sheets, interview sheets, and questionnaire sheets. Subjects in this study amounted to 28 students. The results showed that the data obtained on student learning activeness in using the wordwall application as many as 23 students had very good learning activity with a percentage of 82%, and 5 students had good learning activity with a percentage of 18% in using the wordwall application. From the results of interviews that have been conducted with students, it can be seen that students are more enthusiastic in the learning process using wordwall applications than learning without using learning media.